2009
DOI: 10.1149/1.3205764
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ni/SDC Anode by Alkaline Earth Metal Oxide Addition for Direct Methane-SOFC

Abstract: The anodic performances of Ni/CeO 2 -Sm 2 O 3 (Ni/SDC) modified by the addition of alkaline earth metal oxides (MgO, CaO, SrO, and BaO) were investigated for direct oxidation of CH 4 in solid oxide fuel cells (SOFCs). Although the initial power density of cell with Ni/SDC anode modified by the addition of CaO (Ni-CaO/SDC) was slightly lower than that of cell with Ni/SDC, the former anode exhibited an excellent stability compared to the latter one. After continuous operation of SOFC for 24 h, no or less amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Most of the reported Ni-SDC contains around 50 vol% Ni, similar to Ni-YSZ. We have evaluated Ni/SDC anodes containing no more than 20 wt% Ni [7][8][9][10]. As a result of suppressing Ni aggregation, the 20wt% Ni-SDC anodes exhibited higher anodic performance compared to those containing higher concentrations of Ni.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported Ni-SDC contains around 50 vol% Ni, similar to Ni-YSZ. We have evaluated Ni/SDC anodes containing no more than 20 wt% Ni [7][8][9][10]. As a result of suppressing Ni aggregation, the 20wt% Ni-SDC anodes exhibited higher anodic performance compared to those containing higher concentrations of Ni.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, most methane-fueled SOFC studies with Ni-(doped ceria) composite anodes have been operated with dry or humidified methane fuels (i.e. direct methane oxidation or internal SRM), 11,[25][26][27][28][29] and power generation with internal DRM has rarely been reported. Only recently, Loureiro et al 30 fabricated cermet anodes composed of nickel-copper alloy and gadolinium-doped ceria, and reported that alloying treatment for nickel using copper decreased polarization resistance under a synthetic biogas flow (75% CH 4 and 25% CO 2 ).…”
mentioning
confidence: 99%
“…Furthermore, an examination was made of a calcium-modified Ni-SDC anode, aiming at enhancing coking resistance and CO 2 reactivity by the addition of a basic calcium component. It should be noted that the use of basic oxides (CaO, BaO, SrO) to Ni-based anodes has been widely investigated for SOFCs with dry or humidified methane fuel, 26,27,33,34 but has seldom been tested for SOFCs with internal DRM. According to the literature, enhanced coking resistance in the modified anodes can be ascribed to watermediated oxidation of the deposited carbon 35,36 or suppression of the coke formation by modification of the electronic structure of metallic nickel to a slightly anionic state.…”
mentioning
confidence: 99%